El Problema de agencia entre accionistas en las sociedades por acciones simplificadas colombianas (2016)
ABSTRACT: The present article analyzes the agency problem between minority and majority shareholders of Colombian Simplified Stock Corporation (S.A.S.). For this, the paper proposes a model of game theory to compare the incentives of minority and majority shareholders in the S.A.S. and the Colombian Code of Commerce. Finally presents a solution of agency problem through the institution of abuse of right and measurements of corporate governance.